Kafa’ah among the Hadrami Arabs in the Malay World (Anthropology of Law Approach) - Imam Subchi (Jurnal Cita Hukum, 2020)
AbstractThis article explores how Hadrami Arabs have been maintaining the law of kafa’ah marriage or endogamy marriage in the Malay world—in this instance Indonesia and Malaysia and, to some extent, Singapore—from the early 1990s to the present. Arabs, mostly of Hadrami descent, are carrying their traditions everywhere in their diaspora. Moreover, those traditions are related to the Islamic law of endogamy marriage. This study employs a qualitative research method. Library research is used in collecting data, published or unpublished documents. Data sources are done with a web search using the following databases: Google Scholar, Ebsco-host, Research gate, Sage Journal, Scientific Electronic Library Online (SciELO), and others. The results and discussion of the research explain that the process of the establishment of the tradition of endogamy marriage has begun since their existence in Hadramaut to preserve offspring because they became the target of the murder of the Umayyad dynasty. In Hadramaut, they established Naqabah Asyraf Kubra, which served to record the genealogy and maintain the Syarifah ((female descendants of Prophet Muhammad) to obey the law of endogamy marriage. On the other hand, this paper will also examine issues related to the existence of the Arab community diaspora in the state order in the legal perspective reviewed from the guarantee of its legal certainty. This study concludes that in the end, the issue of Syarifah marriage with this akhwal depends very much on the perspective of the community either from Alawiyyin group or not. Rigid attitudes towards traditions supported by religious propositions will still be able to preserve this. However, how big is the tradition of the law of endogamy marriageable to withstand the onslaught of globalization and modernization that continues to run, because some Syarifah groups question and even break out of or disobey this tradition.Keywords: kafa’ah, syarifah, sayyid, hadrami, nasab  AbstrakArtikel ini menjelaskan bagaimana komunitas Arab Hadrami mempertahankan hukum kawin sekufu’ atau perkawinan endogami di dunia Melayu—seperti di Indonesia, Malaysia, dan Singapura—dari kurun waktu 1990 hingga dewasa ini. Komunitas Arab Hadrami (yang dewasa ini sudah banyak menjadi keturunan), membawa tradisi mereka dimanapun berdiaspora, terlebih lagi tradisi tersebut berkaitan dengan hukum Islam kawin sekufu’. Studi ini menggunakan metode penelitian Pustaka, baik yang sudah atau belum dipublikasi. Sumber data dilakukan dengan pencarian web menggunakan basis data sebagai berikut: Google Scholar, Ebsco-host, Research gate, Sage Journal, Scientific Electronic Library Online (SciELO), dan lain-lain. Temuan penelitian ini adalah bahwa proses pembentukan tradisi hukum pernikahan sekufu’ telah dimulai sejak mereka menjadi incaran pembunuhan dari bani Umayah, dan semakin mapan semenjak keberadaan mereka di Hadramaut, dengan mendirikan Naqabah Asyraf Kubra guna mencatat silsilah dan mempertahankan syarifah agar mentaati hukum perkawinan sekufu’. Disisi lain, tulisan ini juga mengkaji terkait persoalan eksistensi diaspora komunitas arab dalam tatanan kenegaraan dalam persepektif hukum dengan ditinjau dari jaminan kepastian hukumnya. Di pihak lain, persoalan pernikahan Syarifah dengan akhwal atau eksogami sangat bergantung terhadap cara pandang masyarakat baik dari kalangan Alawiyyin maupun bukan. Sikap yang kaku terhadap tradisi yang ditopang oleh dalil-dalil agama akan tetap dapat melestarikan ini. Namun seberapa besar tradisi hukum kawin sekufu’ ini mampu bertahan terhadap gempuran globalisasi dan modernisasi yang terus berjalan, sebab sebagian kelompok syarifah mempertanyakan dan bahkan keluar dari atau tidak menta’ati tradisi ini.Keywords: Kafa’ah, Syarifah, Sayyid, Hadrami, Nasab АннотацияВ этой статье объясняется, как арабское сообщество Хадрами сохраняло закон kawin sekufu (равенства в браке) или эндогамного брака в малайском мире -например, в Индонезии, Малайзии и Сингапуре- с 1990 года по настоящее время. Арабское сообщество Хадрами (у которой сегодня много потомков) несет свои традиции везде, где бы они ни находились в диаспоре, более того, эта традиция связана с исламским законом kawin sekufu. В этом исследовании используются литературные методы исследования, опубликованные и неопубликованные. Результаты этого исследования состоят в том, что процесс формирования закона kawin sekufu был начат, так как они стали объектом убийства Омейядов, и стал более устоявшимся, так как их существование в Хадрамауте, путем создания Naqabah Asyraf Kubra для записи генеалогии и поддержания «Syarifah » в порядке соблюдать закон kawin sekufu. С другой стороны, в данной статье также исследуется вопрос о существовании арабской диаспоры в государственной структуре с правовой точки зрения, рассматривается  с точки зрения ее правовой определенности. Кроме того, вопрос о «Syarifah» с экзогамией сильно зависит от того, как люди относятся к тому и другому, исходя из Alawiyyin (Баалави Сада) или нет. Жесткое отношение к традиции, поддерживаемое религиозными аргументами, все же сможет сохранить эту вещь. Однако насколько сильно традиция закона kawin sekufu может противостоять продолжающемуся натиску глобализации и модернизации, потому что некоторые группы «Syarifah» подвергают сомнению и даже оставляют или не подчиняются этой традиции. Ключёвые Слова: кафа (термин, используемый в области исламской юриспруденции в отношении брака в исламе, что на арабском языке буквально означает равенство или эквивалентность), щерифа (традиционный арабский титул для женщин), сейид (почётный титул у мусульман для потомков пророка Мухаммеда — через его дочь Фатиму и внука Хусейна), хадрами, насаб (патронимическое имя)